Correlation between Diet and Fatty Acid Composition in Serum Premenopausal Women Inhabiting in the City, Farm Village or grassland in Inner Mongolia - KUWAMORI, Toyomi; KAGAMIMORI, Sadanobu; HARADA, Sumiko; SHIMMURA, Tetsuo; ITOMURA, Miho; SEKINE, Michikazu; ZHANG, Miao; BI, Lifu; KUWAMORI, Masanori (Japanese Journal of Health and Human Ecology, 2002)
The aim of the present study was to clarify the relationship between the contents of food and serum fatty acid components in Inner Mongolian. The subjects were 35 premenopausal women aged 35-49 (13 women from a city, 11 from a farming village, and 11 from a grassland area). By using the 24-hour recall method, we evaluated the contents of food and calculated the levels of fatty acid components in food. One-way analysis of variance (ANOVA) were used to evaluate the differences in levels of the content of food and fatty acid components in food among the 3 districts. Multiple regression analysis was used to evaluate the contribution of the contents of food intake to serum fatty acid components. There were significant differences in levels of the contents of food and fatty acid components in food among the 3 districts. The contents of food significantly contributed to the serum levels of n-3 and n-6/n-3 polyunsaturated fatty acids (PUFA). These results indicated that, although the contents of food significantly influenced the serum levels of PUFA in Inner Mongolian, food contributing to the serum PUFA levels was different among the 3 districts.